Supervisi berbasis Islamic Worldview: Studi kasus peningkatan mutu standar Isi di SMP Al-Qur'an - El Hanif, Zubair Qudsi; Suryadin, Ardi; Supraha, Wido; Lisnawati, Santi; Kasmen (Program Studi Magister Pendidikan Agama Islam, 2025)
Supervision based on an Islamic worldview is believed to be capable of improving the quality of content standards in Islamic educational institutions, such as Qur'anic junior high schools. This study was motivated by the crisis faced by Muslims due to internal and external challenges, including the trends of globalisation and secularisation in education, which have shifted society's views away from Islamic values towards a secular worldview. This study aims to analyse the application of Islamic worldview-based supervision in improving content quality standards at Qur'an junior high schools. A qualitative approach was used with a case study method to gain an in-depth understanding of the context and implementation in the field. Data were collected through in-depth interviews, observations, and documentation. The results of the study show that Qur'an junior high schools have made efforts to integrate the general and religious curricula and implement the national curriculum, but there are still weaknesses, including the lack of implementation of the concepts of fardhu 'ain and fardhu kifayah, the suboptimal Islamisation of the national curriculum, and the failure to make the Qur'an the core of the curriculum. The conclusion of this study emphasises the importance of supervision based on an Islamic worldview to strengthen the integration of Islamic values, foster students' faith and noble character, and serve as the basis for curriculum development in Islamic educational institutions. Abstrak Supervisi berbasis Islamic worldview diyakini mampu meningkatkan mutu standar isi pada lembaga pendidikan Islam, seperti SMP Al-Qur’an. Penelitian ini dilatarbelakangi oleh krisis yang dihadapi umat Islam akibat tantangan internal dan eksternal, termasuk arus globalisasi dan sekularisasi pendidikan yang menggeser pandangan masyarakat dari nilai-nilai Islam menuju pandangan dunia sekuler. Penelitian ini bertujuan untuk menganalisis penerapan supervisi berbasis Islamic worldview dalam peningkatan mutu standar isi di SMP Al-Qur’an. Pendekatan yang digunakan adalah kualitatif dengan metode studi kasus untuk memperoleh pemahaman mendalam terhadap konteks dan implementasi di lapangan. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa SMP Al-Qur’an telah berupaya mengintegrasikan kurikulum umum dan agama serta menerapkan kurikulum nasional, namun masih terdapat kelemahan, antara lain belum terimplementasinya konsep fardhu ‘ain dan fardhu kifayah, belum optimalnya Islamisasi kurikulum nasional, serta belum menjadikan Al-Qur’an sebagai inti kurikulum. Simpulan penelitian ini menegaskan pentingnya supervisi yang berlandaskan Islamic worldview untuk memperkuat integrasi nilai keislaman, menumbuhkan iman dan akhlak mulia siswa, serta menjadi dasar pengembangan kurikulum di lembaga pendidikan Islam.